Does Distanced Self-Talk Facilitate Emotion Regulation Across a Range of Emotionally Intense Experiences?. (January 2021) - Orvell, Ariana; Vickers, Brian D.; Drake, Brittany; Verduyn, Philippe; Ayduk, Ozlem; Moser, Jason; Jonides, John; Kross, Ethan
Research indicates that a subtle shift in language—silently referring to oneself using one's own name and non–first-person-singular pronouns (i.e., distanced self-talk)—promotes emotion regulation. Yet it remains unclear whether the efficacy of distanced self-talk depends on the intensity of the negative experience reflected on and whether the benefits extend to emotionally vulnerable individuals. Two high-powered experiments addressed these issues. Distanced as opposed to immersed self-talk reduced emotional reactivity when people reflected on negative experiences that varied in their emotional intensity. These findings held when participants focused on future and past autobiographical events and when they scored high on individual difference measures of emotional vulnerability. The results also generalized across various types of negative events. These findings illuminate the functionality of language for allowing people to regulate their emotions when reflecting on negative experiences across the spectrum of emotional intensity and highlight the need for future research to examine the clinical implications of this technique.